A Highly Distributed CuxAuy‐Deposited Nanotube Carbon for Selective Reduction of NO in the Presence of NH3 at Very Low Temperature. Issue 1 (15th November 2013) - Amrousse, Rachid; Moumni, Said El
Abstract CuxAuy Deposited on carbon nanotubes prepared by solution plasma sputtering was used for first time as a catalyst for selective reduction of NO, in the presence of NH3, at low temperature. N2 and H2O are desirable during the NO reduction process; however, N2O is totally absent from the obtained products.